Properti Psikometrik Skala Academic Burnout, Resilient Coping, dan Spiritualitas/Religiusitas Pada Mahasiswa Muslim - Dina Nazriani; Dwi Dinnur Riszki (Journal of Psychology and Humans, 2026)
Abstract Self-report instruments must demonstrate sound psychometric properties before scores can be meaningfully interpreted. This study examined the item characteristics, internal-consistency reliability, and factor structure of three instruments administered to Muslim university students: the Burnout Assessment Tool (BAT) for academic burnout, the Brief Resilient Coping Scale (BRCS), and a spirituality/religiousness scale based on the IPIP-VIA Spirituality/Religiousness items augmented with Islamic ritual-practice items. A total of 158 students completed all items, which were rated on a five-point scale. Item analysis used corrected item-total correlations, reliability was estimated with Cronbach's alpha and McDonald's omega, and the hypothesized factor structures were tested with confirmatory factor analysis (CFA). All items showed corrected item-total correlations above .30, and every subscale reached good reliability (alpha .77-.91; omega .78-.91). The four-factor BAT core model fit the data acceptably and the BRCS one-factor model fit excellently, whereas the spirituality/religiousness model fit poorly, mainly because of ceiling effects on belief and ritual items. Construct correlations were theoretically coherent: academic burnout related negatively to resilient coping and to spirituality/religiousness, while coping and spirituality/religiousness were positively related. The instruments are reliable and largely valid for this population, with the spirituality/religiousness scale requiring refinement. Keywords: academic burnout, resilient coping, spirituality/religiousness, reliability, confirmatory factor analysis Abstrak Instrumen laporan-diri perlu memiliki properti psikometrik yang memadai sebelum skornya dapat ditafsirkan secara bermakna. Penelitian ini menguji karakteristik item, reliabilitas konsistensi internal, dan struktur faktor tiga instrumen yang diberikan kepada mahasiswa Muslim: Burnout Assessment Tool (BAT) untuk academic burnout, Brief Resilient Coping Scale (BRCS), dan skala spiritualitas/religiusitas yang berbasis item IPIP-VIA Spirituality/Religiousness dengan tambahan item praktik ritual keislaman. Sebanyak 158 mahasiswa menjawab seluruh item yang diukur dengan skala lima poin. Analisis item menggunakan korelasi item-total terkoreksi, reliabilitas diestimasi dengan Cronbach's alpha dan McDonald's omega, serta struktur faktor diuji melalui confirmatory factor analysis (CFA). Seluruh item memiliki korelasi item-total terkoreksi di atas .30 dan setiap subskala mencapai reliabilitas yang baik (alpha .77-.91; omega .78-.91). Model empat-faktor inti BAT memiliki kecocokan yang dapat diterima dan model satu-faktor BRCS sangat cocok, sedangkan model spiritualitas/religiusitas memiliki kecocokan yang kurang baik akibat efek langit-langit pada item keyakinan dan ritual. Korelasi antarkonstruk koheren secara teoretis: academic burnout berkorelasi negatif dengan resilient coping dan spiritualitas/religiusitas, sementara coping dan spiritualitas/religiusitas berkorelasi positif. Instrumen ini reliabel dan sebagian besar valid untuk populasi ini, dengan skala spiritualitas/religiusitas yang masih perlu disempurnakan. Kata Kunci: academic burnout, resilient coping, spiritualitas/religiusitas, reliabilitas, analisis faktor konfirmatori